2015
DOI: 10.1126/scitranslmed.aaa7721
|View full text |Cite
|
Sign up to set email alerts
|

Hurdles in therapy with regulatory T cells

Abstract: Improper activation of the immune system contributes to a variety of clinical conditions, including autoimmune and allergic diseases as well as solid organ and bone marrow transplantation. One approach to counteract this activation is through adoptive therapy with regulatory T cells (Tregs). Efforts to manufacture these cells have led to good maunfacturing practice-compliant protocols, and Treg products are entering early clinical trials. Here, we report the stance of the European Union Cooperation in Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
126
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 61 publications
1
126
0
1
Order By: Relevance
“…Based on what has been described in transplantation clinical trials, the function and application of huTregs are quite promising. Until now, it has been possible to generate protocols for the purification and expansion of huTregs from healthy donors and patients, with the following infusion for treating conditions as transplant rejection, GvHD or autoimmune diseases [1,2,4,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on what has been described in transplantation clinical trials, the function and application of huTregs are quite promising. Until now, it has been possible to generate protocols for the purification and expansion of huTregs from healthy donors and patients, with the following infusion for treating conditions as transplant rejection, GvHD or autoimmune diseases [1,2,4,20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to murine Tregs, huTregs correspond to 5% of Peripheral blood mononuclear cells (PBMC) and express the surface markers CD4, CD25 and low/negative expression of CD127, and transcription factor Forkhead-box P3 (FoxP3), characteristic of murine and human Tregs [1].…”
Section: Introductionmentioning
confidence: 99%
“…As such, various groups developed protocols for isolating and expanding autologous human Tregs [14,23,27]. However, the lack of a definitive human Treg marker and the requirement for compliance with good manufacturing practice (GMP) has meant that Treg therapy is only now moving from the bench to the clinic [14,23,27].…”
Section: Regulatory T-cell Therapy -Current Applicationsmentioning
confidence: 99%
“…Several studies showed promising results using adoptive Tregs (67)(68)(69)(70)(71)(72)(73)(74). However, before adoptive Treg therapy is a cellular therapeutic agent, there are various hurdles to overcome (75). We need to identify and isolate Tregs, and expand them under good manufacturing practice for cellular product manufacturing.…”
Section: How To Incorporate Moga In Transplant-eligible Patients Withmentioning
confidence: 99%